Pyrrolidine dithiocarbamate reverses Bcl-xL-mediated apoptotic resistance to doxorubicin by inducing paraptosis - Park, Seok Soon; Lee, Dong Min; Lim, Jun Hee; Lee, Dongjoo; Park, Sang Jun; Kim, Hwan Myung; Sohn, Seonghyang; Yoon, Gyesoon; Eom, Young Woo; Jeong, Seong Yun; Choi, Eun Kyung; Choi, Kyeong Sook (Carcinogenesis, 2018)
Elevated Bcl-xL expression in cancer cells contributes to doxorubicin (DOX) resistance, leading to failure in chemotherapy. In addition, the clinical use of high-dose doxorubicin (DOX) in cancer therapy has been limited by issues with cardiotoxicity and hepatotoxicity. Here, we show that co-treatment with pyrrolidine dithiocarbamate (PDTC) attenuates DOX-induced apoptosis in Chang-L liver cells and human hepatocytes, but overcomes DOX resistance in Bcl-xL-overexpressing Chang-L cells and several hepatocellular carcinoma (HCC) cell lines with high Bcl-xL expression. Additionally, combined treatment with DOX and PDTC markedly retarded tumor growth in a Huh-7 HCC cell xenograft tumor model, compared to either mono-treatment. These results suggest that DOX/PDTC co-treatment may provide a safe and effective therapeutic strategy against malignant hepatoma cells with Bcl-xL-mediated apoptotic defects. We also found that induction of paraptosis, a cell death mode that is accompanied by dilation of the endoplasmic reticulum and mitochondria, is involved in this anti-cancer effect of DOX/PDTC. The intracellular glutathione levels were reduced in Bcl-xL-overexpressing Chang-L cells treated with DOX/PDTC, and DOX/PDTC-induced paraptosis was effectively blocked by pretreatment with thiol-antioxidants, but not by non-thiol antioxidants. Collectively, our results suggest that disruption of thiol homeostasis may critically contribute to DOX/PDTC-induced paraptosis in Bcl-xL-overexpressing cells.
Keywords: Animals; Antineoplastic Agents; Apoptosis; bcl-X Protein; Carcinoma, Hepatocellular; Cell Line, Tumor; Doxorubicin; Drug Resistance, Neoplasm; Humans; Liver Neoplasms; Male; Mice; Mice, Inbred BALB C; Mice, Nude; Pyrrolidines; Thiocarbamates; Xenograft Model Antitumor Assays